Assessing the effect of green training on agricultural cooperatives willingness to adopt green practices - Cruz, Liezel S. (Journal of Economics, Management & Agricultural Development, 2018)
This study aims to examine the effect of green training on the decision of agricultural cooperatives to adopt green practices...